2020
DOI: 10.1007/s00291-020-00606-9
|View full text |Cite
|
Sign up to set email alerts
|

An interval efficiency analysis with dual-role factors

Abstract: Data envelopment analysis (DEA) is a data-driven and benchmarking tool for evaluating the relative efficiency of production units with multiple outputs and inputs. Conventional DEA models are based on a production system by converting inputs to outputs using input-transformation-output processes. However, in some situations, it is inescapable to think of some assessment factors, referred to as dual-role factors, which can play simultaneously input and output roles in DEA. The observed data are often assumed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 44 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…According to Scopus data, till July 2021, more than 60 articles (published in journals and conferences) have been found which did research in this area using various MCDM methods as well as mathematical models. Most of the authors consider this as a MCDM problem and used a wide variety of methods such as analytic hierarchy process (AHP) (Abdel-Basset et al , 2021; Zarbakhshnia et al , 2020; Govindan et al , 2019; Ilgin, 2017; Prakash and Barua, 2016; Khodaverdi and Hashemi, 2015; Senthil et al , 2014), analytic network process (ANP) (Tavana et al , 2018; Tavana et al , 2016), technique for order performance by similarity to ideal solution (Abdel-Basset et al , 2021; Govindan et al , 2019; Ilgin, 2017; Prakash and Barua, 2016; Senthil et al , 2014), stepwise weight assessment ratio analysis (Zarbakhshnia et al , 2018; Mavi et al , 2017), multi-objective optimization on the basis of ratio analysis (Zarbakhshnia et al , 2020; Mavi et al , 2017) and data envelopment analysis (DEA) (Toloo et al , 2021; Momeni et al , 2015; Saen, 2011) to solve it. Some authors developed this problem as a modelling problem and used various theories and programming tool to solve it.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Scopus data, till July 2021, more than 60 articles (published in journals and conferences) have been found which did research in this area using various MCDM methods as well as mathematical models. Most of the authors consider this as a MCDM problem and used a wide variety of methods such as analytic hierarchy process (AHP) (Abdel-Basset et al , 2021; Zarbakhshnia et al , 2020; Govindan et al , 2019; Ilgin, 2017; Prakash and Barua, 2016; Khodaverdi and Hashemi, 2015; Senthil et al , 2014), analytic network process (ANP) (Tavana et al , 2018; Tavana et al , 2016), technique for order performance by similarity to ideal solution (Abdel-Basset et al , 2021; Govindan et al , 2019; Ilgin, 2017; Prakash and Barua, 2016; Senthil et al , 2014), stepwise weight assessment ratio analysis (Zarbakhshnia et al , 2018; Mavi et al , 2017), multi-objective optimization on the basis of ratio analysis (Zarbakhshnia et al , 2020; Mavi et al , 2017) and data envelopment analysis (DEA) (Toloo et al , 2021; Momeni et al , 2015; Saen, 2011) to solve it. Some authors developed this problem as a modelling problem and used various theories and programming tool to solve it.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When collecting self-reported data on behaviour, the main focus is on their final presentation, since, in many cases, respondents are not able to clearly express their judgments, and it is assumed that all final values derived from such data are uncertain [21]. Recently, in an uncertain DEA framework, imprecise DEA approaches [22], fuzzy DEA methods [23], and robust DEA methods [24] have been used. In [25,26], it was shown that both imprecise DEA and fuzzy DEA models can give robust composite index scores, which implies the effectiveness and reliability of these two approaches for modelling qualitative data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In estimating the efficiency of each DMU by their model, a dual-role factor can simultaneously take both input and output roles, but in the previous DEA models, after the evaluation, a dual-role factor can only take one role. Toloo et al [35] presented DEA models in the presence of dual-role factors for the interval data. The formulated models are a pair of mixed binary linear programming problems to calculate the relative efficiencies in the interval forms.…”
Section: Introductionmentioning
confidence: 99%